Fuel cell fundamentals - O'Hayre, Ryan P.; Cha, Suk-Won 1971-; Colella, Whitney G.; Prinz, F. B. (John Wiley & Sons Inc., 2016)
Fuel Cell Fundamentals provides a thorough introduction to the principles and practicalities behind fuel cell technology. Beginning with the underlying concepts, the discussion explores fuel cell thermodynamics, kinetics, transport, and modeling before moving into the application side with guidance on system types and design, performance, costs, and environmental impact. This new third edition has been updated with the latest technological advances and relevant calculations, and enhanced chapters on advanced fuel cell design and electrochemical and hydrogen energy systems. Worked problems, illustrations, and application examples throughout lend a real-world perspective, and end-of-chapter review questions and mathematical problems reinforce the material learned. Fuel cells produce more electricity than batteries or combustion engines, with far fewer emissions. This book is an essential introduction to the technology that makes this possible, and the physical processes behind this cost-saving and environmentally friendly energy source.